2009
DOI: 10.1086/598520
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Severe Respiratory Disease Associated with Emergent Human Adenovirus Serotype 14 at a US Air Force Training Facility in 2007

Abstract: Emergence of Ad14, a rare Ad serotype, caused a protracted outbreak of respiratory illness among military recruits. Most infected recruits experienced FRI or milder illnesses. Some required hospitalization, and 1 died. Natural Ad7 infection may protect against severe Ad14 illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
118
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 31 publications
2
118
0
3
Order By: Relevance
“…However, the low rate of infections (5%) observed by Esposito et al ( 11 ) in household contacts of persons infected with the emerging virus suggests that infection is unlikely to spread in the community. Efficient transmission of HAdV-14p1 appears to require close physical contact, as supported by the observation that in barracked communities used for military trainees in the United States, antibody titers demonstrated recent exposure after entry to the facility ( 25 ). Of interest in the HAdV-14p1 cases identified in the present study is the higher frequency of male patients (78%) infected; this observation has been reported by other groups ( 19 , 26 ), although the numbers identified in our study are insufficient to make definitive conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…However, the low rate of infections (5%) observed by Esposito et al ( 11 ) in household contacts of persons infected with the emerging virus suggests that infection is unlikely to spread in the community. Efficient transmission of HAdV-14p1 appears to require close physical contact, as supported by the observation that in barracked communities used for military trainees in the United States, antibody titers demonstrated recent exposure after entry to the facility ( 25 ). Of interest in the HAdV-14p1 cases identified in the present study is the higher frequency of male patients (78%) infected; this observation has been reported by other groups ( 19 , 26 ), although the numbers identified in our study are insufficient to make definitive conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…Past studies in the United States reported that adenovirus epidemics were associated with preventive interventions such as adenovirus vaccines and hand washing (8,22). However, the association of adenovirus epidemics with the types and difficulties of military training has remained uncertain in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were young, previously healthy soldiers. Although several studies have described the clinical features of adenovirus infection among military personnel (7)(8)(9)(10)(11)(12)(13), few studies have compared the clinical characteristics of pneumonic and non-pneumonic adenovirus cases or evaluated the risk factors associated with military training courses. Furthermore, few reports have provided detailed descriptions of the radiological features of adenovirus infections by means such as thinsection computed tomography (CT) (7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no vaccine available for the civilians. However, there is a vaccine against type 4 and 7, available on the license, only for U.S. military recruits [14].…”
Section: Introductionmentioning
confidence: 99%